(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
A persons outlook on research is important to understand when teams are developing healthcare policies and clinical standards. Often there are conflicts as physicians, healthcare workers, analysts and others bring unique knowledge systems together. Epistemology, the possible ways of gaining knowledge of social realities, is a term which policy analysts can better understand to support the policy development process.